Education and the Body in Europe (1900-1950) movements, public health, pedagogical rules and cultural ideas - Hopfner, Johanna 1959-; Polenghi, Simonetta; Németh, András 1950-; Kasper, Tomáš 1974- (Peter Lang, 2021)
The public dimension of the body became paramount in the first half of the 20th century, when the image of the modern man, with his virile stereotypes, became a cliché, in strict connection with nation building first and totalitarian ideologies later. Yet, different cultural and educational trends advocated for life reform and liberation of the body. Both the metaphorical and the material body were invested by cultural, religious, political and educational theories and practices with strong links and similarities but also national differences
Keywords: Geschichte 1900-1950; Pädagogik; Reform; Gesundheitserziehung; Soziale Bewegung; Kultur; Körper; Leibeserziehung; Europa; Aufsatzsammlung